Legal Protection of Children as Victims of Domestic Violence According to Positive Law - Annisa, Kurnia; Muwahid, Muwahid (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2024)
Legal protection of children who are victims of domestic violence (KDRT) must be considered carefully by all relevant parties. The purpose of this research is to see from the point of view of positive law in Indonesia in an effort to protect children who are victims of domestic violence. TLegal protection of children who are victims of domestic violence (KDRT) must be considered carefully by all relevant parties. The purpose of this research is to see from the point of view of positive law in Indonesia in an effort to protect children who are victims of domestic violence. This research method uses normative juridical research with an analysis of statutory and conceptual approaches by looking at several relevant laws, books and literature. The results show that children who are victims of domestic violence have been fully protected by the Indonesian legal system. However, its implementation still faces several challenges, such as low public awareness, less than optimal coordination between institutions and limited rehabilitation facilities. Therefore, sustainable efforts are needed to improve legal protection for child victims of domestic violence. Several strategies can be carried out starting from improving laws and regulations, increasing public awareness and strengthening institutional cooperation his research method uses normative juridical research with an analysis of statutory and conceptual approaches by looking at several relevant laws, books and literature. The results show that children who are victims of domestic violence have been fully protected by the Indonesian legal system. However, its implementation still faces several challenges, such as low public awareness, less than optimal coordination between institutions and limited rehabilitation facilities. Therefore, sustainable efforts are needed to improve legal protection for child victims of domestic violence. Several strategies can be carried out starting from improving laws and regulations, increasing public awareness and strengthening institutional cooperation